Distinctive Gene Expression Profiles and Effectors Consistent With Host Specificity in Two Formae Speciales of Marssonina brunnea - Ren, Fei; Yan, Dong-Hui; Wu, Guanghua; Sun, Xiaoming; Song, Xiaoyu; Li, Ruhua (Frontiers in Microbiology, 2020)
The knowledge on the host specificity of a pathogen underlying an interaction is becoming an urgent necessity for global warming. In this study, the gene expression profiles and the roles of effectors in host specificity were integrally characterized with two formae speciales, multigermtubi and monogermtubi, of a hemibiotrophic pathogen Marssonina brunnea when they were infecting respective susceptible poplar hosts. With a functional genome comparison referring to a de novo transcriptome of M. brunnea and Pathogen–Host Interaction database functional annotations, the multigermtubi strain showed abundant and significant differentially expressed unigenes (DEGs) (more than 40%) in colonizing the initial invasion stage and in the necrotrophic stage. The monogermtubi strain induced less than 10% of DEGs in the initial invasion stage but which abruptly increased to more than 80% DEGs in the necrotrophic stage. Both strains induced the least DEGs in the biotrophic stage compared to the initial invasion and necrotrophic stages. The orthologs of the effector genes Ecp6, PemG1, XEG1, ACE1, and Mg3LysM were exclusively induced by one of the two formae speciales depending on the infection stages. Some unigenes homologous to carbohydrate lytic enzyme genes, especially pectate lyases, were notably induced with multigermtubi forma specialis infection but not expressed in the monogermtubi forma specialis at an earlier infection stage. The extraordinary differences in the functional genome level between the two formae speciales of M. brunnea could be fundamental to exploring their host specificity determinant and evolution. This study also firstly provided the fungal transcriptome of the monogermtubi forma specialis for M. brunnea.